Helicobacter pylori Screening After Acute Myocardial Infarction The Cluster Randomized Crossover HELP-MI SWEDEHEART Trial - Hofmann, Robin; James, Stefan; Sundqvist, Martin O.; Wärme, Jonatan; Angerås, Oskar; Alfredsson, Joakim; Erlinge, David ; 0000-0003-3042-5766; Arefalk, Gabriel; Arstad, Göran; Blomberg, Simon; Fröbert, Ole; Hambraeus, Kristina; et al. (JAMA, 2025)
IMPORTANCE Upper gastrointestinal bleeding is common after myocardial infarction. OBJECTIVE To determine whether routine screening for Helicobacter pylori infection during hospitalization for myocardial infarction reduces bleeding events and improves clinical outcomes. DESIGN, SETTING, AND PARTICIPANTS A nationwide, open-label, 2-period, 2-sequence, cluster randomized, crossover clinical trial using a clinical registry for study population definition and data collection merged with national Swedish health data registries. From November 17, 2021, through January 17, 2024, thirty-five Swedish hospitals grouped into 18 clusters were randomized to a sequence of 1 year with routine H pylori screening of all patients with acute myocardial infarction followed by a washout period of 2 months before crossing over to 1 year with usual care or vice versa. Patients were followed up until January 17, 2025. INTERVENTION Routine addition of H pylori screening by urea breath test to standard care in all patients hospitalized for myocardial infarction during the screening periods. MAIN OUTCOME AND MEASURE Upper gastrointestinal bleeding, analyzed by a negative binomial model in the intention-to-treat population. RESULTS A total of 18 466 patients (median age, 71 years [IQR, 61-79], 13 138 males [71%]) with myocardial infarction were followed up: 9245 during the screening periods and 9221 during the nonscreening periods. At admission, 2284 during the screening periods and 2275 during the nonscreening periods (both 24.7%) reported proton pump inhibitor use. During screening periods, 6480 patients (70%) had undergone testing, of those 1532 (23.6%) tested positive for H pylori. After a median follow-up of 1.9 years, 299 patients in the screening group (incidence rate, 16.8 events per 1000 person-years; cumulative hazard at 3 years, 4.1%) and 336 in the usual care group (incidence rate, 19.2 events per 1000 person-years; cumulative hazard at 3 years, 4.6%) experienced the primary end point of upper gastrointestinal bleeding (rate ratio [RR], 0.90; 95% CI, 0.77-1.05; P = .18). Predefined nonmultiplicity adjusted subgroup analyses showed a heterogeneous intervention effect; for no anemia (RR, 0.98; 95% CI, 0.80-1.21), mild anemia (RR, 0.64; 95% CI, 0.42-0.98), and moderate to severe anemia (RR, 0.44; 95% CI, 0.23-0.87; P for interaction = .03). CONCLUSIONS AND RELEVANCE Among unselected patients with acute myocardial infarction, routine H pylori screening did not significantly reduce the risk of upper gastrointestinal bleeding.